UZBEKISTAN MUSIC AND INSTRUMENTS OF THE 18TH – 19TH CENTURIES - Tolqinova Gulsanam Gulumovna, (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
The article provides a scientific analysis of the development of classical music and folk musical instruments in the territory of Uzbekistan during the 18th–19th centuries (the period of the Bukhara Emirate, Khiva and Kokand Khanates). Special attention is paid to the formation and flourishing of the Bukhara Shashmaqom (six maqams) as the brightest example of maqam art, its integration with poetic texts and Sufi ghazals, as well as the mutual influence of folk and court music. The main instruments – dutar, tanbur, rubab, sato, ghijak, chang, nay, surnay, karnay and doira – are examined in detail: their construction, performance techniques, role in ensembles and cultural significance. The processes of democratization of musical life, the emergence of literary-musical circles and the beginning of notation under the influence of Russian ethnography are also covered.